Infrared Studies of Some Sensitive Vibrational Modes of Pyridines on Complex Formation with Halogens and Interhalogens - Baruah, S.K. (Asian Journal of Chemistry, 2016)
Complexes of 2-bromopyridine, 3-chloropytidine, β-picoline and α-picoline with halogens and interhalogens along with their positive halogen salts have been prepared and characterized. The most sensitive vibration modes have been studied in methylene chloride solution in order to see the mutual influences of donors and acceptor properties. The frequency shift in Br2-complexes is found to be larger than that of the I2-complexes and explained on the basis of back transfer of charge from πg-antibonding orbital of bromine to the lowest π-orbital of the donors. The bonding order has been observed to be I2 < IBr < ICl < coordinated iodine (I): Br2 < BrCl < coordinated bromine (I) and α-picoline > β-picoline > 3-chloropytidine > 2-bromopyridine.